FEM modeling on the compaction of Fe and Al composite powders - Han, Peng; An, Xizhong; Zhang, Yuxi; Zou, Zongshu (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
The compaction process of Fe and Al composite powders subjected to single action die compaction was numerically modeled by FEM method. The relationship between the overall relative density and compaction pressure of the compacts with various Al contents was firstly identified, and the influences of Al content on the local relative density, stress, and their distributions were studied. Then the compaction pressure effects on the above properties with fixed Al content were discussed. Furthermore, detailed flow behaviors of the composite powders during compaction and the relationship between the compaction pressure and the ejection force/spring back of the compact were analyzed. The results show that: (1) With each compaction pressure, higher relative density can be realized with the increase of Al content and the relative density distribution tends to be uniform; (2) When the Al content is fixed, higher compaction pressure can lead to composite compact with higher relative density, and the equivalent Von Mises stress in the central part of the compact increases gradually; (3) Convective flow occurs at the top and bottom parts of the compact close to the die wall, each indicates a different flow behavior; (4) The larger the compaction pressure for each case, the higher the residual elasticity, and the larger the ejection force needed.